THE EFFECT OF FINACIAL PERFORMNACE TO CORPORATE VALUJE WITH THE DISCLOSURE OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY AS MODERATING VARIABLE - Guido S; Hexana Sri Lastanti; Murtanto Murtanto (Business and Entrepreneurial Review, 2014)
This research is done to know effects of financial performance toward corporate value by using the disclosure of Good Corporate Governance and Corporate Social Responsibility as a moderating variable. ROA, ROE, and Leverage as an indicator of financial performance is known as the independent variable. Company value measured by Tobin’s is known as the dependent variable. Good Corporate Governance(GCG) and Corporate Social Responsibility (CSR) is moderating variable.The companies that are in this research are manufacturing companies which are listed in the Indonesia Stock Exchange (IDX) starting from 2004 until 2007, published financial statements ending 31 December, and had complete data of Good Corporate Governance and Corporate Social Responsibility. The data is then processed by using statistical appliance that are called regression with interaction.According to the research, the financial performance (ROA and leverage) has an effect on corporate value. Disclosure of Corporate Social Responsibility(CSR) does not affect to financial performance (ROA and Leverage) toward the value of the company. Disclosure of Good Corporate Governance (GCG) affects the financial performance of relationship (ROA and Leverage) toward the value of the company.